Impact of the Agulhas Return Current on the oceanography of the Kerguelen Plateau region, Southern Ocean, over the last 40 kyrs. (1st January 2021) - Civel-Mazens, M.; Crosta, X.; Cortese, G.; Michel, E.; Mazaud, A.; Ther, O.; Ikehara, M.; Itaki, T.
Abstract: The oceanography of the western Indian sector of the Southern Ocean is extremely complex due to the presence of several subantartic islands and plateaus that alter the zonal flow of the Antarctic Circumpolar Current. The circulation is even more complex around the Kerguelen Islands (KI) as the hydrological fronts merge with the Agulhas Return Current, the latter transporting warm surface waters from the low latitudes to the Subantarctic Zone (SAZ) east of KI. Here we present new sea-surface and sub-surface temperatures, based on diatom and radiolarian census counts respectively, in two cores covering the last 40, 000 years (40 kyrs) to infer past oceanographic changes in the KI region. In core MD11-3353, located in the Polar Front Zone (PFZ) west of KI, both sea-surface and sub-surface temperatures follow the expected glacial-interglacial pattern, with a constant difference of ∼3 °C, suggesting that the structure of the top 500 m of the water column did not change drastically over this period. In core MD12-3396CQ, located in the SAZ east of KI, the sub-surface temperature record again follows the expected glacial-interglacial pattern while the diatom-based reconstruction shows a strong warming during the 40-24 kyrs period, with a mean difference between the two of ∼9 °C. The temperature difference subsequently reverts to ∼3 °C during the glacial termination and Holocene. We suggest that the large difference between surface and sub-surface temperatures during the 40-24 kyrs period resulted from the injection of warm surface waters from the Indian low latitudes. This signal was transported to the core site by a strengthened Agulhas Return Current during the glacial, when the Agulhas leakage to the Atlantic was reduced. Our study thus proposes that the surface conditions in the SAZ of the KI region are shaped by the interplay between the migration of the Southern Ocean hydrological fronts and the Agulhas (Return) Current, both being climatically modulated. Highlights: Comparison of diatom SST and radiolarian sub-ST reconstructions in two SIO cores. High SST anomaly in the Eastern Kerguelen surface SAZ between 40 and 24 kyrs. Climate-driven fronts' migrations regulated the Agulhas Return Current intensity. Strengthened Agulhas Return Current over MIS 3 - MIS 2 warming Indian surface SAZ.